2020
DOI: 10.1021/acs.jpcb.0c01744
|View full text |Cite
|
Sign up to set email alerts
|

Cu(I) Controls Conformational States in Human Atox1 Metallochaperone: An EPR and Multiscale Simulation Study

Abstract: Atox1 is a human copper metallochaperone that is responsible for transferring copper ions from the main human copper transporter, hCtr1, to ATP7A/B in the Golgi apparatus. Atox1 interacts with the Ctr1 C-terminal domain as a dimer, although it transfers the copper ions to ATP7A/B in a monomeric form. The copper binding site in the Atox1 dimer involves Cys12 and Cys15, while Lys60 was also suggested to play a role in the copper binding. We recently showed that Atox1 can adopt various conformational states, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 81 publications
1
24
0
Order By: Relevance
“…In conclusion, the CW-EPR experiments suggest that the Cys15 residue is important for Atox1 dimerization, while Cys12 is important for protein stability in the presence of Cu(I), suggesting that Cys12 is critical for Cu(I) binding. Multi-scale MD simulations were carried out to confirm this [101]. These simulations also identified Cys12 as a critical residue for Cu(I) binding, while coordination of Cu(I) with Cys15 could be exchanged.…”
Section: Identifying Metal Coordination Sitesmentioning
confidence: 76%
See 2 more Smart Citations
“…In conclusion, the CW-EPR experiments suggest that the Cys15 residue is important for Atox1 dimerization, while Cys12 is important for protein stability in the presence of Cu(I), suggesting that Cys12 is critical for Cu(I) binding. Multi-scale MD simulations were carried out to confirm this [101]. These simulations also identified Cys12 as a critical residue for Cu(I) binding, while coordination of Cu(I) with Cys15 could be exchanged.…”
Section: Identifying Metal Coordination Sitesmentioning
confidence: 76%
“…To better identify the two different conformations, we performed additional DEER experiments as a function of pH, together with efforts relying on computational methods. We assigned the distribution around 2.8 nm to an "open structure", a conformation in which the two C12 residues of the Atox1 dimer are involved in Cu(I) binding, and the C15 residues do not necessarily coordinate to Cu(I) [101]. In the "closed conformation", corresponding to the 4.5 nm distribution, all four cysteine residues, i.e., C12 and C15 from both monomers, coordinate to the Cu(I) ion.…”
Section: Following Conformational Changes In Biomolecules Upon Metal Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Atox1 is a soluble protein of 68 amino acids, which captures Cu(I) by directly interacting with the C-terminal 188 HCH end of hCtr1. Atox1 coordinates one Cu(I) ion with the cysteine (Cys15) residues of the conserved 12 CXX 15 C motif in Atox1 dimerization [30][31][32].…”
Section: Cu Chaperones In Intracellular Cddp Traffickingmentioning
confidence: 99%
“…A recent study on Atox1, employing double electron–electron resonance (DEER) measurements, showed complex distance distributions with a wealth of peaks related to several positions in the dimer 9 . In addition, another study employed hybrid quantum mechanics‐molecular mechanics (QM/MM) and molecular dynamics (MD) methods to investigate the copper binding in Atox1 10 . In this work, the relevant copper‐binding residues and the Cu(I) ion itself were treated as QM while the rest of the system was calculated using MM.…”
Section: Introductionmentioning
confidence: 99%